ASSESSMENT PRACTICES AMONG TURKISH PHYSIOTHERAPISTS: A CROSS SECTIONAL STUDY OF TIME ALLOCATION, METHODS, AND BARRIERS TO EFFECTIVE CLINICAL EVALUATION - Hilal Aslan; Zeynep Arıkan; Mert Sürmelioğlu; Rabia Tuğba Tekin (Gazi Sağlık Bilimleri Dergisi, 2026)
Background: Accurate and systematic patient assessment is foundation of effective physiotherapy practice. Aim: The aim of this study is to determine the frequency of assessment, how much time physiotherapists in Turkey spend in clinics, which methods they use, and to investigate the barriers for physiotherapists to perform assessment. Methods: The data collection process was completed with an online questionnaire prepared on Google Forms. Information regarding evaluation processes and barriers was obtained from physiotherapists' own perspectives. Results: While 94.5% (n: 189) of the physiotherapists stated that they evaluated their patients for the first time only, 35% (n: 70) reported allocating less than 10–20 minutes for evaluation. Additionally, 56.5% (n: 113) stated that they did not use a standardized form during evaluations. A total of 79% (n: 158) indicated using more than one method, and 67% (n: 134) preferred low-cost measurement tools during patient assessment. Physiotherapists reported that the greatest barrier to adequately assessing their patients was “lack of time” (37.5%; n: 75). Conclusion: It is important that physiotherapists working one-to-one and for long periods with diverse patient groups have the necessary means and facilities for a successful assessment process, as effective assessment is necessary for a successful treatment program.